Relevansi Sikap Profetik dengan Dimensi Idealisme Pancasila: Sistem Nilai Dalam Menghadapi Tekanan Ekonomi Dan Mental Selama Pandemi Covid-19 - Muhammad Thohir; Muhammad Hamdan Za’imuddin; Izza Nur Fuadina; Ayu Laila Fitri (Muhammadiyah University of Mataram, 2021)
The Indonesian people are facing economic impacts and mental pressure due to the increasingly threatening attacks of the Covid-19 outbreak. However, Indonesia is a religious and nationalist nation, which has a strong value system based on the religious norms and ideology of Pancasila.Therefore, the purpose of this study is to explain, what, why and how to strengthen the prophetic attitudes and idealism dimension of the Pancasila to be built in order to deal with the economic and psychological pressures of the people affected by COVID-19. By using a qualitative approach, the researcher chooses the library research method, namely the study of various sources of literature relevant to the purpose of the study. Literature data obtained were analyzed both textually, contextually and contextually. The results showed that the prophetic attitude and dimensions of Pancasila idealism are a highly relevant, mutually reinforcing value system, especially in facing the threat of the Covid-19 outbreak, both from an economic perspective and mental challenges. The relevance of prophetic attitudes and dimensions of Pancasila idealism here as character strengthening are able to present a values system that can be called as moderative idealism, not right idealism, nor left idealism.